Development of new code for optical code division multiple access systems - Hilal Adnan, Fadhil (Universiti Malaysia Perlis, 2011)
The main arguments for using Optical Code Division Multiple Access (OCDMA) are the flexibility of an asynchronous access method, increased security and graceful degradation. Over the last decade, many codes were proposed for the OCDMA, especially for Spectral Amplitude Coding (SAC). Proper code selection is very important for good system performance and high network scalability with low bit-error rates (BERs) of less than 10−9. OCDMA systems, however, generally, suffer from multiple access interference (MAI) noise which originated from other simultaneous users severely increases the likelihood of occurrence of bit errors. To mitigate this limitation, spectral amplitude coding (SAC) OCDMA is used throughout this thesis. The advantage of SAC-OCDMA over conventional OCDMA systems is that, when using appropriate detection technique, the MAI can totally be suppressed. This either reduces the effect of MAI or improves the performance even in the presence of MAI. This work proposed algorithms for designing a new code with variable cross-correlation properties for the SAC-OCDMA system, namely, Random Diagonal (RD) code. The overall code sequences are divided into two parts: code and data segments. These codes sequences having zero and variable cross-correlation at data segment and code segment, respectively. The significant contribution of this code is the suppression of MAI and improved system performance by guaranteeing zero crosscorrelation at data segment between code sequences. Spectral direct detection technique is proved, which improves the performance of the RD code. The study is carried out using a theoretical calculation, and simulation experiment. The simulations are carried out using various design parameters namely; distance, bit rate, input power and chip spacing. By comparing the theoretical and simulation results taken from the commercial optical systems simulator “OptisystemTM“, it is shown that utilizing RD code considerably improves the system performance compared with other SAC codes such as Hadamard, Modified Quadratic Congruence (MQC), and Modified Frequency Hopping (MFH) codes. Given the almost unlimited bandwidth of OCDMA, Fiber-To-The Home (FTTH) technology is seen as an ideal way of "future-proofing" networks in light of the ever-increasing consumer and business demand for faster networks and higher-bandwidth applications. Four aspects are tackled in this research. Firstly, a comprehensive discussion takes place on all important aspects of existing codes from advantages and disadvantages point of view. Splitting algorithm is proposed to construct the new code families namely RD code. The existing code families are being challenged by several problems such as poor cross correlation properties, a rather restricted number of available code sequences, complicated and time consuming code construction. To overcome the stated problems, RD code families are used throughout this stage. Secondly, a new detection technique based on spectral direct detection is developed and compared to the reported detection techniques. Such a scheme allows using sequences with less strict in-phase cross correlation constraints, thus allowing much larger code families to be constructed. For the performance analysis, the effects of phase-induced intensity noise (PII ), shot noise, and thermal noise are considered simultaneously. The performances of the system compared to reported systems were characterized by referring to the signal to noise ratio (S R), the bit error rate (BER) and the effective power (Psr). umerical results show that, the new detection scheme based on the RD code families can suppress the intensity noise power, and improve the system performance significantly compared to the reported systems. Employing RD code not only provide to have a better BER performance than other codes, but was able to be used for a large number of users at different rates of transmission with costeffective light sources, and for longer transmission distances. Thirdly, a software simulation for SAC OCDMA system with the RD families using a commercial optical system, “OtisystemTM Ver. 7.0” is conducted. Simulation results show that the RD code is very much suitable for a point-to-point FTTH transmission in an access network. Finally, an experimental test to generate and characterize the RD code using the light emission diode (LED) and Fiber Ring Laser as optical sources for OCDMA systems is discussed. The limitations of the RD code should be highlighted in this thesis; these limitations are considered the main disadvantages of the RD code, which are: the system weight should be greater or equal to three; and using the spectral direct detection scheme the overall system is considered less secure compared with other SAC-OCDMA detection schemes.